The Effect of 1T Phase Molybdenum Disulfide on the Tribological Performance of Polyethylene Glycol. Issue 7 (3rd August 2022) - Li, Ning; Guo, Shihao; Pan, Bingli; Xie, Mengxin; Yan, Junjiang; Chen, Zhe
Abstract: In our research described in this paper 1T Phase Molybdenum Disulfide/Polyethylene Glycol (200) (1T-MoS2 /PEG) was studied as a lubricant for steel-steel contact with the goal of minimizing or eliminating galling. The morphology and structures of 1T-MoS2 were analyzed by various techniques, such as scanning electron microscopy (SEM), X-ray diffraction spectroscopy (XRD), and X-ray photoelectron spectroscopy (XPS). In addition, the friction performance of oleic acid (OA) modified 1T-MoS2 as a lubricants additive for PEG was investigated. The results of the friction test indicated that the average friction coefficient and wear scar diameter of PEG containing 0.1875 wt% 1T-MoS2 were 14.30% and 46.90% less than those of pure PEG, respectively. However, those of 0.1875 wt% 1T-MoS2 /PEG modified by OA as lubrication additives were 47.83% and 56.79% lower than those of pure PEG. 1T-MoS2 nanoparticles can not only fill the inherent grooves on the surface of the steel ball, but also form a friction lowering film on the friction interface, thus reducing friction and wear, which was seen from the results of scanning electron microscopy (SEM) and element mapping of the wear scar. This study, most importantly, provides a foundation for the use of 1T-MoS2 /PEG and OA/1T-MoS2 /PEG as effective lubricants to reduce the friction problems in the mechanical industry.